The potential of video game in Malay language learning for foreign students in a public higher education institution - Alias, Norlidah; Rosman, Fuziah; Abd. Rahman, Mohd.Nazri; Dewitt, Dorothy (Elsevier, 2015)
Public Higher Education Institution (PHEI).The main objective is to consolidate the opinions of experts on types of video games,predicted year of appearance, and suitability of types of video games. Fuzzy delphi (FDM) is mainly used to consolidate a consensus of selected 30 experts from various disciplines and backgrounds. The administered instrument consists of 35 sub items across three themes.The findings show that the experts have reached consensus on items 1.1 to 3.5, with defuzzification value of 0.640 to 0.727. It is found that narrative genre, and platformer games are suitable for foreign learners to learn Malay language. The results also suggest that computer-based video games will not be the trend in Malay language learning from 2024 to 2028 (defuzzification value of 0.727). Instead, augmented reality games and Mobile learning will be dominant trends in future. The findings also show that expert consensus was reached on the effectiveness of video games in developing vocabulary of Malay language (defuzzification value of 0.693). In short, the experts “strongly agreed” that video game is potentially effective in teaching Malay language for foreign learners in the selected PHEI.